Large anion incorporation to improve the performance of large, paper based conducting polymer supercapacitors - Jain, B.; Krishnamoorthy, K. (Materials Today Energy, 2017)
Poly(3,4-ethylenedioxythiophene) (PEDOT) is a stable conducting polymer, hence its dispersion is widely used in commercial devices. However, PEDOT's charge storage properties are not impressive. Thus, improvement in charge storage properties of PEDOT will render the possibility of fabricating stable energy storage devices such as supercapacitors. A fundamentally different approach is required to achieve this objective. We envisioned that the charge storage property of PEDOT can be improved by trapping large anions. These ions would facilitate better ion transport into the PEDOT matrix from the electrolyte and increase the efficiency of supercapacitors. Furthermore, a large anion such as triiodide is relatively immobile in the polymer matrix, hence we hypothesize the ions to be trapped in the polymer. To test this hypothesis, triiodide trapped PEDOT based supercapacitors are fabricated on paper substrates. A 1 cm2 triiodide incorporated PEDOT based supercapacitor exhibited a specific capacitance of 486 F/g. On the other hand, PEDOT without triiodide incorporation exhibited a specific capacitance of 221 F/g. Indeed, a device with an area of 32 cm2 exhibited a specific capacitance of 476 F/g.
Keywords: Flexible Supercapacitors; Paper based Supercapacitors; polyphenols

Organocatalytic Enantioselective Vinylogous Michael-Aldol Cascade for the Synthesis of Spirocyclic Compounds - Jain, B. (Electrochimica Acta, 2017)
Nanoscopic spheres of poly(3,4-ethylenedioxythiophene) from its poly(styrene sulfonate) stabilised dispersion was converted to nanofibers by acid treatment. The nanofibers showed a conductivity of 1800 S/cm. The specific capacitance of nanofiber based supercapcitors increased by 10 times compared to nanospeheres. The specific capacitance and power density were found to be 288 F/g and 9491 W/kg.